Strategies for software exports from developing countries. - Correa, Carlos M. (World Development)
Discusses the economics of software development and the factors that influence the viability of an export-oriented software industry in developing countries. Experiences of a number of Latin American and Asian countries; Focus on India as the main software exporter in the developing world; Software export strategies and their relative advantage to developing countries.